CONTENT-BASED INSTRUCTION STRATEGIES TO IMPROVE ENGLISH MAJOR STUDENTS´ L2 WRITING SKILLS COMMAND: Productive skills development - Mantilla, Marcia; Andrade, Christian (Ecos de la Academia, 2021)
English major students must deal with the assimilation of subject contents while developing foreign language skills. This might be particularly challenging for all the actors involved, considering the future foreign language teachers´ L2 command, especially regarding productive skills and, more specifically, their ability to express themselves though writing. The purpose of this study is to establish the effect of Content-Based Instruction on learners´ writing skills development. This qualitative-quantitative research was carried out during the semester October 2018-February 2019, with fourth level English Major students, at Universidad Técnica del Norte, Facultad de Educación, Ciencia y Tecnología. Surveys were administered and tests were taken by twenty-seven students.  The data collected was processed and, based on the results obtained, the effects of the application of Content-Based Instruction on the improvement of students´ writing skills were analysed.
Keywords: Content Based Instruction, foreign language, writing skills.